Hepatotoxic Effect of Methotrexate on Serum Hepatic Enzymes with Amendment by Sulforaphane in Albino Rats - Kaneez Fatima, Sadia Sundus, Erum Khan, Asma Aijaz, Abdul Samad Khan, Bisma Samad Khan, (Pakistan Journal of Medical & Health Sciences, 2023)
Objective: To evaluate the variations in serum levels of hepatic enzymes in methotrexate damaged hepatic tissue with improvement by sulforaphane. Design of research study: Experimental research study. Duration of research study: this research study was piloted in BMSI, JPMC & total period was one week & three days. Materials and Methods: For research work 40 adult albino rats of 0.2-0.3kg were selected. Time period for final study was 1 week and 3 days because animals started dying after 10 days due to hepatotoxic effect of methotrexate. Animals were separated into 4 groups, A1 was control, B1 animals were Injected Methotrexate intraperitoneally. C1 animals were Injected Methotrexate intraperitoneally along with sulforaphane by N/G. D1 animals was given sulforaphane by N/G. At the end of study, animals were sacrificed & blood was taken by direct cardiac puncture and send for lab investigation. Results: B1 animals presented with significant increase in serum levels of hepatic enzymes while C1 animals had slightly raised serum levels of hepatic enzymes. Practical Implication: These findings contribute further support to the hypothesis that variations in serum levels of hepatic enzymes in methotrexate damaged hepatic tissue are improved by sulforaphane administration. Conclusion: Research accomplishes that sulforaphane altered the unfavorable effects of methotrexate. Group B1 had substantial raise in serum levels of hepatic enzymes whereas Group C1 serum had substantial decrease in serum levels of hepatic enzymes So our recommendation is that sulforaphane should be use with methotrexate to reduce its side effects. Keywords: Aspartate aminotransferase (AST), alanine aminotransferase (ALT), alkaline phosphatase (ALP), lactate dehydrogenase (LDH), reactive oxygen species (ROS), methotrexate(MTX), glutathione (GSH), NADPH (nicotinamideadenine dinucleotide phosphate).